2005
DOI: 10.1111/j.1365-2958.2005.04923.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetratricopeptide repeats in the type III secretion chaperone, LcrH: their role in substrate binding and secretion

Abstract: SummaryNon-flagellar type III secretion systems (T3SSs) transport proteins across the bacterial cell and into eukaryotic cells. Targeting of proteins into host cells requires a dedicated translocation apparatus. Efficient secretion of the translocator proteins that make up this apparatus depends on molecular chaperones. Chaperones of the translocators (also called class-II chaperones) are characterized by the possession of three tandem tetratricopeptide repeats (TPRs). We wished to dissect the relations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 90 publications
5
73
0
1
Order By: Relevance
“…To the contrary, the C-terminal YopD 278-292 peptide is readily soluble and forms an amphipathic a-helix in solution [18]. The binding site of YopD was postulated to localize to a large surface on the model of SycD, the opposite side of the YopB interactions [19], in agreement with data for a common chaperone of YopD and YopB [16].…”
supporting
confidence: 73%
“…To the contrary, the C-terminal YopD 278-292 peptide is readily soluble and forms an amphipathic a-helix in solution [18]. The binding site of YopD was postulated to localize to a large surface on the model of SycD, the opposite side of the YopB interactions [19], in agreement with data for a common chaperone of YopD and YopB [16].…”
supporting
confidence: 73%
“…The spatial distribution of P1, P2, and P3 and the residues forming these pockets are conserved in SycD (Table S3). Indeed, mutations in the predicted pockets of LcrH, IpgC homologue from Yersinia pseudotuberculosis, affect binding and/or secretion of its substrates (26). Together, these observations indicate that the spatial distribution of P1, P2, and P3 is a key feature in TTSS class II chaperones.…”
Section: Resultsmentioning
confidence: 71%
“…In this study, escA was demonstrated to function as a specific chaperone for EseC. EscA possesses the (Neyt & Cornelis, 1999;Waterman & Holden, 2003;Zurawski & Stein, 2003;Edqvist et al, 2006). EspD in EPEC requires two chaperones (CesD and CesD2) for complete secretion and accumulation activities (Neves et al, 2003;Waterman & Holden, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct functional classes of chaperones exist for NF-T3SSs: class I chaperones, which bind to effectors, and class II chaperones, which bind to translocons (Page & Parsot, 2002;Parsot et al, 2003). Class I chaperones share a moderate degree of sequence homology, with a common mixed a/b-helical fold (Parsot et al, 2003;Pallen et al, 2005), while some class II chaperones have been recently reported to share TPR-like motifs (Bröms et al, 2006;Edqvist et al, 2006;Büttner et al, 2008). Interactions of class II chaperones and their substrates are necessary for functions involving regulatory, structural and effector mechanisms (Delahay & Frankel, 2002;Olsson et al, 2004), while some class II chaperones are reported to have defined regions that interact with their cognate substrates (Daniell et al, 2003;Edqvist et al, 2006).…”
Section: Introductionmentioning
confidence: 99%